In vitro propagation of Cinchona officinalis L from seeds - Lima Jiménez, Nelson Ramiro (2018)
Plant micropropagation is a useful tool for the conservation of threatened forest species with the use of in vitro culture techniques. The main objective was to study the in vitro propagation of Cinchona officinalis L from seeds. NaOCl was applied at different concentrations and immersion times for seed disinfection, medium MS (Murashige and Skoog) was supplemented with GA3 for seed germination and for in vitro multiplication phase was used the combination of auxin and cytokinins in different concentrations. The treatments with NaOCl at 50 % for 5, 10 and 15 min were those that obtained the lowest percentage of contamination; the highest percentage of germination in the seeds was obtained with 1 mg/l of GA3 and the best results in vitro multiplication were obtained with the combination of 0.2 NAA + 2.0 BAP. In vitro propagation protocols were generated in the species Cinchona officinalis L with the purpose of undertaking conservation programs and recovering native forest ecosystems of the southern region of Ecuador.